Beyond the Debye length in high ionic strength solution: direct protein detection with field-effect transistors (FETs) in human serum - Chu, Chia-Ho; Sarangadharan, Indu; Regmi, Abiral; Chen, Yen-Wen; Hsu, Chen-Pin; Chang, Wen-Hsin; Lee, Geng-Yen; Chyi, Jen-Inn; Chen, Chih-Chen; Shiesh, Shu-Chu; Lee, Gwo-Bin; Wang, Yu-Lin (Scientific reports, 2017)
In this study, a new type of field-effect transistor (FET)-based biosensor is demonstrated to be able to overcome the problem of severe charge-screening effect caused by high ionic strength in solution and detect proteins in physiological environment. Antibody or aptamer-immobilized AlGaN/GaN high electron mobility transistors (HEMTs) are used to directly detect proteins, including HIV-1 RT, CEA, NT-proBNP and CRP, in 1X PBS (with 1%BSA) or human sera. The samples do not need any dilution or washing process to reduce the ionic strength. The sensor shows high sensitivity and the detection takes only 5 minutes. The designs of the sensor, the methodology of the measurement, and the working mechanism of the sensor are discussed and investigated. A theoretical model is proposed based on the finding of the experiments. This sensor is promising for point-of-care, home healthcare, and mobile diagnostic device.